(untitled) - Fox, Marye Anne (Boston, 1994)
Contents: Structure and bonding in Alkanes; chromatography and spectroscopy; elimination reactions; polymeric materials; molecular basis for drug action.
Keywords: Chemistry, Organic; Hóa học, vô cơ